Cytogenetic evaluation of 20 primary breast carcinomas - Cavalli, L. R.; Cavaliéri, L. M B; Ribeiro, L. A. [UNESP]; Cavalli, I. J.; Silveira, R.; Rogatto, Silvia Regina [UNESP] (Springer Nature, 1997)
Chromosome analysis was performed on samples from 20 Brazilian patients with breast cancer. All the samples were from untreated patients who presented the clinical symptoms for months or years before surgical intervention. Six cases showed axillary lymph node metastases. Clonal chromosome abnormalities were detected in all cases. The numerical alterations most frequently observed involved the loss of chromosomes X, 19, 20, and 22 followed by gain of chromosomes 9 and 8. Among the structural anomalies observed, there was preferential involvement of chromosomes 11, 6, 1, 7, 3, and 12, supporting previous reports that these chromosomes may harbour genes of importance in the development of breast tumors. Two cases with a family history of breast cancer had in common total or partial trisomy 1.
Keywords: axillary lymph node; brazil; breast cancer; chromosome 1; chromosome 11; chromosome 12; chromosome 19; chromosome 20; chromosome 22; chromosome 3; chromosome 6; chromosome 7; chromosome 8; chromosome 9; clinical article; cytogenetics; female; human; lymph node metastasis; male; numerical chromosome aberration; partial trisomy; structural chromosome aberration; X chromosome; Adult; Aged; Aged, 80 and over; Brazil; Breast Neoplasms; Breast Neoplasms, Male; Carcinoma, Ductal, Breast; Chromosome Aberrations; Chromosome Disorders; Chromosome Mapping; Chromosomes, Human; Female; Humans; Karyotyping; Lymphatic Metastasis; Male; Middle Aged; Neoplasms; Trisomy; X Chromosome